Transcription Factors and Plants Response to Drought Stress: Current Understanding and Future Directions - Joshi, Rohit; Wani, Shabir H.; Singh, Balwant; Bohra, Abhishek; Dar, Zahoor A.; Lone, Ajaz A.; Pareek, Ashwani; Singla-Pareek, Sneh L. (Frontiers in Plant Science, 2016)
Increasing vulnerability of plants to a variety of stresses such as drought, salt and extreme temperatures poses a global threat to sustained growth and productivity of major crops. Of these stresses, drought represents a considerable threat to plant growth and development. In view of this, developing staple food cultivars with improved drought tolerance emerges as the most sustainable solution towards improving crop productivity in a scenario of climate change. In parallel, unraveling the genetic architecture and the targeted identification of molecular networks using modern “OMICS” analyses, that can underpin drought tolerance mechanisms, is urgently required. Importantly, integrated studies intending to elucidate complex mechanisms can bridge the gap existing in our current knowledge about drought stress tolerance in plants. It is now well established that drought tolerance is regulated by several genes, including transcription factors (TFs) that enable plants to withstand unfavorable conditions, and these remain potential genomic candidates for their wide application in crop breeding. These TFs represent the key molecular switches orchestrating the regulation of plant developmental processes in response to a variety of stresses. The current review aims to offer a deeper understanding of TFs engaged in regulating plant’s response under drought stress and to devise potential strategies to improve plant tolerance against drought.